1991
DOI: 10.1002/bjs.1800780107
|View full text |Cite
|
Sign up to set email alerts
|

Proximal gastric vagotomy: Follow-up at 10–20 years

Abstract: From August 1969 to December 1989, 600 patients had elective proximal gastric vagotomy for duodenal ulceration with an operative mortality of 0.2 per cent. Of these, 372 patients had surgery over 10 years ago. Three hundred and forty-two patients survived for more than 10 years and, in a prospective study, 305 were reviewed, forming the basis of this 10-20-year follow-up report. Forty-six (15 per cent) have had recurrent ulceration; 80 per cent of these developed symptoms within 5 years and no patient has had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Several authors from Europe and North America, and also we in more than 1200 cases, have shown that it is the operation that best maintains gastric physiology with few side effects and almost no operative mortality [7][8][9][10]. After more than 20 years of its use, the recurrence rate is about 1% each year, with a reduction of peak acid output in around 60% compared to preoperative values [11][12][13].…”
mentioning
confidence: 99%
“…Several authors from Europe and North America, and also we in more than 1200 cases, have shown that it is the operation that best maintains gastric physiology with few side effects and almost no operative mortality [7][8][9][10]. After more than 20 years of its use, the recurrence rate is about 1% each year, with a reduction of peak acid output in around 60% compared to preoperative values [11][12][13].…”
mentioning
confidence: 99%
“…The dissection is then directed towards the left border of the oesophagus and the angle of His The fat pad of the cardio-oesophageal junction containing the anterior vagus nerve is raised to the right and upwards. At least [5][6] cm of the lower Oesophagus should be skeletonized. After dissection of the neurovascular bundles in the anterior layer of the lesser omentum, it is necessary to dissect the middle part of the lesser omentum.…”
Section: Operative Techniquementioning
confidence: 99%
“…Concommitently, the aforementioned untoward effects of truncal vagotomies are nearly eliminated (9,10). Recurrence rates of between 5 and 15% are reported in the literature for this procedure (8).…”
Section: Introductionmentioning
confidence: 99%